Social Media Influencers, Social Environment, Lifestyle, and Financial Management of Generation Z - Laila Dina Nofiana; Anna Widiastuti (Golden Ratio of Finance Management, 2026)
This study explores the role of social media influencers, social environment, and lifestyle in shaping financial management behaviour among Generation Z. The rapid development of social media has increased young people's exposure to financial information, online consumption trends, and digital payment systems, which may influence how they manage their finances. This research employs a quantitative approach using a survey of 200 Generation Z respondents in Jepara Regency. Data were analysed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that social environment and lifestyle have a positive and significant influence on financial management behaviour, while social media influencers do not show a significant effect. These results suggest that interpersonal interactions and daily consumption patterns play a more important role in shaping financial behaviour than digital influencer exposure. The study provides practical implications for financial education programs by highlighting the importance of strengthening social support systems and promoting responsible lifestyle habits among young individuals.